Targeted Delivery of Curcumin to Polyethylene-Induced Osteolysis by Magnetically Guided Zoledronate-Anchored Poly Lactic-Co-Glycolic Acid Nanoparticles via Repressing NF-κB Signaling - Li, Jingyi; Niu, Chengcheng; Jiang, Zichao; Zhang, Zhen; Pan, Yixiao; Xing, Qiqi; Guo, Qi; An, Senbo; Hu, Yihe; Wang, Long (Frontiers in Pharmacology, 2020)
Aseptic loosening induced by periprosthetic osteolysis (PPO) is the leading complication of total joint arthroplasty (TJA) and results in patients having to receive revision surgery. However, there is still no efficient drug to prevent or even slow the pathological process. Herein, we report novel dual-targeted, curcumin-loaded PLGA nanoparticles (ZSCNPs) to inhibit polyethylene-induced osteolysis. These ZSCNPs have good biocompatibility and excellent bone binding affinity. Under external magnetic field guidance, the ZSCNPs can specifically target osteolytic sites with sustained curcumin release, efficiently suppress the effect of IκB kinase (IKK), subsequently inhibit activation of the NF-κB signaling pathway, and ultimately prevent osteoclast formation and particle-induced osteolysis. Therefore, these novel dual-targeted, drug-loaded nanoparticles could be applied as a useful strategy for targeted treatment of PPO after TJA.